Reducing Resistance Training Volume during Ramadan Improves Muscle Strength and Power in Football Players - Rebaï, H.; Chtourou, H.; Zarrouk, N.; Harzallah, A.; Kanoun, I.; Dogui, M.; Souissi, N.; Tabka, Z. (International Journal of Sports Medicine, 2014)
We aimed to examine the effect of maintaining or reducing resistance training volume during Ramadan-intermittent-fasting (RIF) on short-term maximal performances. 20 footballers (age: 18.4±0.8 years; body-mass: 72.4±4.1 kg; height: 183.4±4.6 cm) were matched and randomly assigned to a normal-training-group (G1) or a tapering-group (G2). They were tested for muscular strength (maximal-voluntary-contraction) and power (squat-jump and counter-movement-jump) 1 month before RIF (T0), 1 week before RIF (T1), after 2 weeks of fasting (T2) and at the end of RIF (T3). From T1 to T2, subjects performed a whole-body resistance training program (8-repetitions×4-sets with 4-min recovery in-between). During RIF, G1 maintained the same training program, while G2 performed a period of reduced training volume (3 sets/exercise; − 22%). Muscle strength and power increased significantly from T0 to T1, from T0 to T2 and from T0 to T3 in G1 and G2 and from T1 to T2 and from T1 to T3 only in G2 (p<0.05). Performance was higher in G2 than G1 during T2 (p<0.01). Moreover, the ∆-change of performance between T0 and T2 and T3 was significantly higher in G2 than G1 (p<0.05). For young soccer players, a tapering period characterized by a reduced training volume during RIF may lead to significant improvement in muscle strength and power.
Keywords: Ramadan; taper; training volume; muscle power; muscle strength